182k views
4 votes
Question 10 of 12, Step 1 of 29/14CorrectConsider the following quadratic equation:3.x2 - 13x + 2 = -2Step 1 of 2: Using the standard form ax2 + bx + c = 0 of the given quadratic equation, factor theleft hand side of the equation into two linear factors.AnswerKeypadKeyboard Shortcuts= 0

User Turin
by
6.3k points

1 Answer

4 votes

Solution

- The question would like us to solve the quadratic equation:


3x^2-13x+2=-2

- The solution to this equation is given below:


\begin{gathered} 3x^2-13x+2=-2 \\ \text{Add 2 to both sides} \\ 3x^2-13x+4=0 \\ \\ \text{ We can rewrite the x-term as follows:} \\ -13x=-12x-x \\ \\ 3x^2-12x-x+4=0 \\ Let\text{ us factorize} \\ \\ 3x(x-4)-1(x-4)=0 \\ (x-4)\text{ is common } \\ \\ (x-4)(3x-1)=0 \end{gathered}

- Thus, the linear factors are


undefined

User Sbg
by
7.1k points